Pattern of Spheroidal Degeneration of Cornea and Its Association with Other Eye Diseases at Anterior Segment Clinic in Menelik II Tertiary Referral Hospital - Tesfay K; Shibeshi MA (Clinical Ophthalmology, 2024)
Kiros Tesfay, Menen Ayalew Shibeshi Department of Ophthalmology, School of Medicine, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Kiros Tesfay, Email kirostesfay@ymail.comPurpose: The purpose of the study was to assess the pattern of spheroidal degeneration of cornea (SDC) and its association with other eye diseases at the anterior segment clinic (ASC) in Menelik II Tertiary Referral Hospital.Methods: A hospital-based prospective descriptive study was conducted at ASC, in Menelik II Tertiary Referral Hospital, from May 2021 to September 2022. All enrolled patients meeting the inclusion criteria were selected and assessed with a structured questionnaire. Descriptive analysis was used to describe the study variables in terms of frequency and percentage. The results were presented using tables and figures.Results: Out of 62 cases of SDC, 48 (77.4%) were male and 14 (22.6%) were female. It was more prevalent in the age groups of 60– 69 and 70– 79. Most respondents had outdoor activity (91.9%). A total of 24.2% of patients were found to have Stage I; 35.5% were found to have Stage II; and 40.3% were in Stage III. Posterior subcapsular cataract (PSC) was found in 10 (16.1%) SDC cases, post-trachomatous corneal opacity (CO) in 10 (16.1%) SDC cases, and non-trachomatous CO in 8 (12.9%) SDC cases, but none of them had an association with SDC.Conclusion: Between May 2021 and September 2022, sixty-two cases of SDC were found at the ASC in Menelik II Tertiary Referral Hospital. The data showed a preponderance of SDC in males and older subjects. Stage III and primary types are the leading presentations. It was observed predominantly in individuals who spent most of their time outdoors. Pterygium, corneal opacity, pseudoexfoliation (PXF), PSC, and glaucoma were noted; however, none of these had a significant association with SDC.Keywords: corneal opacity, pseudoexfoliation, pterygium, outdoor, spheroidal degeneration of cornea, stage